2007
DOI: 10.1073/pnas.0704452104
|View full text |Cite
|
Sign up to set email alerts
|

The hidden structure of overimitation

Abstract: Young children are surprisingly judicious imitators, but there are also times when their reproduction of others' actions appears strikingly illogical. For example, children who observe an adult inefficiently operating a novel object frequently engage in what we term overimitation, persistently reproducing the adult's unnecessary actions. Although children readily overimitate irrelevant actions that even chimpanzees ignore, this curious effect has previously attracted little interest; it has been assumed that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
585
2
11

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 555 publications
(667 citation statements)
references
References 28 publications
39
585
2
11
Order By: Relevance
“…It is possible that young children do not show the additive type of ratchet effect at all. Indeed, there is a growing literature on young children's tendency to "overimitate" or copy others "too" faithfully (e.g., Flynn, 2008;Lyons, Young, & Keil, 2007;Nielsen & Tomaselli, 2010), and this tendency might well hinder them from coming up with innovations. Indeed, in our rice carrying task, all first-generation children copied the adult's use of the most inefficient tool, the small piece of cardboard, when it was demonstrated pedagogically.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that young children do not show the additive type of ratchet effect at all. Indeed, there is a growing literature on young children's tendency to "overimitate" or copy others "too" faithfully (e.g., Flynn, 2008;Lyons, Young, & Keil, 2007;Nielsen & Tomaselli, 2010), and this tendency might well hinder them from coming up with innovations. Indeed, in our rice carrying task, all first-generation children copied the adult's use of the most inefficient tool, the small piece of cardboard, when it was demonstrated pedagogically.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this tendency is so strong that some researchers have even coined the term 'ritual stance' to capture the fact that when children do not see a clear goal to an actor's action, they imitate even more precisely than if they do see a goal -presumably because the lack of a goal signals a noninstrumental function for the action, which therefore (given that it is being demonstrated) may be of cultural importance (e.g., [5,6]). Also tellingly, human children, but not great apes, copy even irrelevant parts of an action sequence in acts of so-called 'overimitation' ( [7]; see also [8]). And most tellingly of all, human children, but not great apes, conform to others even in situations when they have to override a previously successful strategy to do so, so-called 'strong conformity' [9 ,10 ].…”
Section: Imitative Learningmentioning
confidence: 99%
“…The child is then instructed to remove the toy from the box as fast as possible. Despite the explicit time constraints, children still imitated both the rational and irrational actions (e.g., the demonstrator stroking the box with a feather), even though the irrational actions were clearly unrelated to the goal (Horner & Whiten, 2005;Lyons et al, 2007).…”
Section: Overimitation Behaviormentioning
confidence: 99%
“…Social cues, such as demonstrator status, have been shown to modulate overimitation. For example, it has been shown that children will only reproduce irrational actions when being observed by the demonstrator (Lyons et al, 2007;Nielsen & Blank, 2011). This suggests that overimitation is an important social behavior, and motivates us to explore its neural mechanisms.…”
Section: Overimitation Behaviormentioning
confidence: 99%
See 1 more Smart Citation